Efectos de la Glosectomía Parcial en el desarrollo ocluso maxilar: Estudio experimental - Núñez Paiva, Edith (2003)
This is an experimental, prospective and longitudinal study, where it was evaluated influence of the tongue on occluso-maxillary growth of the pigs. We took four 1-month-old pigs. They were separated in control and experimental groups. Initial cefalometric radiograph was taken in both groups. Then, experimental group pigs were partially glossectomized. After one month and a half we took another cefalometric radiograph in control and experimental group. We observed that mandibular and maxillary growth was significantly reduced lengthwise. It was seen a disminished inclination of mandibular incisors in glossectomized animals compared to control group.